Efectos del clormequat en cultivares resistentes y susceptibles a sequía de cereales de primavera [Sorghum bicolor, Zea mays] - Rojas Garcidueñas, M; Gámez, H (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Sorghum and maize, both susceptible and resistant to drought, were treated before planting by immersing the seeds in chlormequat 4000 ppm then grown in plastic bags with 1 kg soil in the greenhouse in such a manner that water was lost by transpiration only. Chlormequat determined reduction in height and leaf area. Also water loss was reduced by chlormequat but this effect was apparent in drought susceptible plants only. It seems therefore, that under drought conditions there is the alternative of either using a drought, resistant cultivar or using a susceplible one treated with chlormequat, but no advantage is obtained from the application of chlormequat to drought, resistant cultivars.